Opsoclonus-Myoclonus Outcome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
The developmental outcome of 11 patients with opsoclonus-myoclonus, 8 having occult neuroblastoma, is reported from the Division of Pediatric Neurology, Children's Memorial Hospital, Chicago.